Finite Element Analysis of Impact-Velocity Effects on the Erosion Behavior of GH4720Li Superalloy-Based Cr₃C₂ Coatings - Riki Hendra Purba; Raffi Indrajati; Fitri Wahyuni; James Julian; Elvi Armadani; Fathin Muhammad Mahdhudhu (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2026)
This study examines the effect of impact velocity on the erosion behavior of GH4720Li superalloy with and without Cr₃C₂–NiCr coating using Finite Element Analysis. Silica particles (0.7 mm) were modeled at velocities of 25–125 m/s under normal impact. Results show that increasing velocity raises the maximum Von Mises stress before reaching a dynamic equilibrium. Coated specimens exhibited nearly twice the stress values of uncoated ones, indicating better load distribution and initial damage resistance. At low velocities (25–50 m/s), the coating reduced plastic deformation by absorbing impact energy. However, at higher velocities (≥75 m/s), the coating transferred more energy to the substrate, causing greater plastic strain than in uncoated material. These findings demonstrate that cermet coatings improve erosion resistance at low-to-moderate velocities but have limited performance under high-velocity impacts